2012
DOI: 10.1254/jphs.12r02cp
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of Calcitonin Gene-Related Peptide^|^ndash;Containing Nerve Innervation

Abstract: Abstract. Calcitonin gene-related peptide (CGRP) is a major neurotransmitter and CGRPcontaining primary sensory neurons play an important role in nociception and potent vasodilation. CGRP-containing nerves in mesenteric arteries are decreased in pathological animal models (hypertension, diabetes, and atherosclerosis). In apolipoprotein E-knockout mice, which have atherosclerosis and peripheral sensory nerve defects, nerve growth factor (NGF)-mediated CGRP nerve facilitation was down-regulated, which may have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 26 publications
2
16
0
Order By: Relevance
“…We found no evidence of an increase in sensory fibre innervation in the adult SHR. Also we found no evidence of decreased CGRP functionality in the posterior cerebral arteries of adult SHR, as reported for dorsal root ganglia or mesenteric arteries (Supowit et al 2001;Hashikawa-Hobara et al 2012).…”
Section: Role Of Sympathetic Nerves In Remodelling Of Vertebrobasilarsupporting
confidence: 73%
“…We found no evidence of an increase in sensory fibre innervation in the adult SHR. Also we found no evidence of decreased CGRP functionality in the posterior cerebral arteries of adult SHR, as reported for dorsal root ganglia or mesenteric arteries (Supowit et al 2001;Hashikawa-Hobara et al 2012).…”
Section: Role Of Sympathetic Nerves In Remodelling Of Vertebrobasilarsupporting
confidence: 73%
“…CGRP is produced in both peripheral and central neurons and is a potent peptide vasodilator that can function in the transmission of pain [9]. In a spinal cord injury, CGRP is derived from motor neurons and plays a role in nerve regeneration after injury.…”
Section: Discussionmentioning
confidence: 99%
“…In a spinal cord injury, CGRP is derived from motor neurons and plays a role in nerve regeneration after injury. Conversely, CGRP is derived from dorsal root ganglion when synthesized in the dorsal horn of the spinal cord and may be involved in transmission of post-injury pain [9]. Previous studies showed that CGRP stimulates specific progenitor cells, which secrete an insulin-like growth factor, leading to regeneration [22], and CGRP represses specific immune cells, such as T lymphocytes, via repression of IL-2 and nuclear factor-kB [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using experimental models of hypertension, it has been reported that CGRP-containing nerves in mesenteric arteries are decreased [128]. In addition, capsaicin-induced hypertension can be mediated by decreased vasodilatation (CGRP, kinin, or prostaglandin) or by a direct action on vascular smooth muscle [129].…”
Section: The Role Of Cgrp On Some Vascular-related Diseasesmentioning
confidence: 99%